QR code based two-factor authentication to verify paper-based documents - Maysaa Abd Ulkareem Naser; Eman Talib Jasim; Haider M. Al-Mashhadi (Universitas Ahmad Dahlan, 2020)
Important paper-based documents Exposed to forgery such as: official certificates, birth, marriage, death certificates, selling and buying documents and other legal documents is more and more serious and sophisticated. With the purposes of fraud, appropriation of property, job application and assignment in order to swindle public authorities, this forgery has led to material loss, belief deterioration as well as social instability. There are many techniques has been proposed to overcome this issues such as: ink stamps, live signatures, documented the transaction in third party like the court or notary. In this paper, it’s proposed a feasible solution for forgery prevention for paper-based documents using cloud computing application. With the application of Quick Response bidirectional barcode and the usage of hash algorithm. The study aims at developing an electronic verification system for official and issued books (documents, endorsements, and other official books) to/from different sections of the Institute using QR technology.